Poor Physical Performance Is Associated with Postoperative Complications and Mortality in Preoperative Patients with Colorectal Cancer - Sánchez-Torralvo, Francisco José; González-Poveda, Iván; García-Olivares, María; Porras, Nuria; Gonzalo-Marín, Montserrat; Tapia Guerrero, María José; Mera-Velasco, Santiago; Toval-Mata, José Antonio; Ruiz López, Manuel; Carrasco-Campos, Joaquín; Santoyo-Santoyo, Julio (IOAP-MPDI, 2022)
Introduction: Poor physical performance has been shown to be a good predictor of complications in some pathologies. The objective of our study was to evaluate, in patients with colorectal neoplasia prior to surgery, physical performance and its relationship with postoperative complications and in-hospital mortality, at 1 month and at 6 months. Methods: We conducted a prospective study on patients with preoperative colorectal neoplasia, between October 2018 and July 2021. Physical performance was evaluated using the Short Physical Performance Battery (SPPB) test and hand grip strength (HGS). For a decrease in physical performance, SPPB < 10 points or HGS below the EWGSOP2 cut-off points was considered. Nutritional status was evaluated using subjective global assessment (SGA). The prevalence of postoperative complications and mortality during admission, at 1 month, and at 6 months was evaluated. Results: A total of 296 patients, mean age 60.4 ± 12.8 years, 59.3% male, were evaluated. The mean BMI was 27.6 ± 5.1 kg/m2. The mean total SPPB score was 10.57 ± 2.07 points. A total of 69 patients presented a low SPPB score (23.3%). Hand grip strength showed a mean value of 33.1 ± 8.5 kg/m2 for men and 20.7 ± 4.3 kg/m2 for women. A total of 58 patients presented low HGS (19.6%). SGA found 40.2% (119) of patients with normal nourishment, 32.4% (96) with moderate malnutrition, and 27.4% (81) with severe malnutrition. Postoperative complications were more frequent in patients with a low SPPB score (60.3%vs38.6%; p=0.002) and low HGS (64.9%vs39.3%, p=0.001). (...)
Keywords: Cáncer colorrectal; Physical performance; Malnutrition; Cancer; Oncology; Colorectal; Surgery